Suspicious of the Filipino Social Virtue of Fortitude - Nalupta, Monica Jalandoni (Perspective in the Arts and Humanities ASIA (formerly Asian Perspectives in the Arts and Humanities), 2016)
This article argues that virtue takes on particular color or texture in specific social contexts. In the case of the Filipino context, the virtue of fortitude is Thomistic, Second, it will argue that it is necessary to engage in a social-ethical critique of social virtue, arguing that since the Philippines concept of fortitude lacks a crucial link with justice it can be considered deficient. The article is concerned with critiquing the form that virtue has assumed in the Philippines, as well as the abuse of ethical language in discussions of virtue. In the Philippines society, the language of virtue is used to promote resilience, but also passive suffering, and this paves the way for injustice to flourish.